Single Phase Seven Levels Cascaded inverter Driven in real time using ( DS1104 – Dspace ) platform (Damascus University Journal for engineering sciences, 2021)
Multi level inverters can be used to build better voltage wave shape, making use of serial and parallel connection of electronic elements, to reach the needed high voltages and powers.So they are used in high voltage, and high power applications .In this paper, a design and implementation for a single phase, seven levels laboratory type cascaded inverter, using (Matlab/Simulink) program for modeling and simulation , and data acquisition and control (DSPACE -DS1104 Platform), with its monitoring and control program (Control-Desk).A computer model for a single phase seven levels cascaded inverter was designed, consisted of  power circuit and drive pulses circuit, and the results of modeling and simulation was recorded,   Then, the same drive pulses circuit was implemented to drive a real power circuit, which was implemented and developed with all needed drive and insulation circuit, to implement a laboratory type, single phase, seven levels cascaded inverter, driven by DS1104 system ,and running in real time through (DSP processors).The real results were saved ,and  compared with simulation results.
Keywords: Control in real time; Matlab/Simulink program; DSP processors; DSPACE-DS1104) platform with (Control Desk) program